A qualitative study in Gauteng to investigate if CSR contributes to brands being top of mind awareness to consumers’ and how this affects buying behaviours. - Madondo, Nokuthula (The IIE, 2015)
This research will explore brand perception with regards to Corporate Social Responsibility (CSR) in the South African context. In the early 1990’s CSR was driver to many changes needed and happening in the country and still continues to be a driver of change. Brand positioning with the use of CSR has become a critical objective and aim for organisations as consumers have started to associate brand credibility with transparency. How an organisation behaves across its value chain, including CSR has an impact on how the brand is perceived and also guides consumer interaction. The environment, society and economy should be part of every organisations list of importance, financial gain should not be the driver in organisations but rather a result of organisations behaving ethically and improving the environment.
Keywords: Corporate Social Resonsibility; Value Chain; Branding; Brand Positioning